PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Umar, Sumardi; Harlina, Harlina (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This research investigates the influence of corporate scale and earnings capacity on a company’s market valuation, which serves as a primary indicator of organizational success. Investor perception, which is represented in the company's stock price and overall performance, is used to assess firm worth. A literature review is the methodology employed, and thirty pertinent papers were chosen based on factors such publications from 2013 to 2024 and their applicability to the research issue. Research confirms that business size significantly influences firm value, as larger organizations frequently command higher prices and better investor sentiment. Additionally, it has been demonstrated that profitability significantly affects business value, with high profitability being a sign of efficient performance and resource management. The study's practical implications for businesses are that they must concentrate on boosting profitability in order to draw in investors and raise firm value, while its theoretical implications suggest that firm size and profitability should be taken into account in business valuation models.